Communication Strategy in Enhancing Competence of Health Counseling Officers and Awareness on Maternal and Child Health in Rural Community in West Java Province - El Karimah, Hj. Kismiyati; Sugiana, Dadang; Venus, Anter; Setiaman, Agus (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The research entitled, "Communication Strategy in Enhancing Competence of Health Counseling Officers and Awareness on Maternal and Child Health in Rural Community in West Java Province," Maternal Mortality Rate (MMR) to date is still being used as indicator of women’s health status in Indonesia. Having to consider the importance of MMR , the efforts that are directed at reducing maternal and infant mortality rate have been incorporated into the Millennium Development Goals (MDGs) No. 5 Based on the health census data shows that West Java Province still has high maternal and infant mortality rate, this is inversely proportional with other achievements that achieved remarkably by this province which is also known as the buffer of this capital city of Jakarta. The research indicates that the disparity in mortality rates considerably vary in a country as geographically diverse as Indonesia. Bandung for example is highland surrounded by a string of mountains and still challenged by inequality in health facilities. Medical personnel and health services are more concentrated in urban areas diluting proper health presence in underserved rural areas. Other factor based on our findings shows that medical personnel resources management and their competence are also challenging. The team will focus on micro scale that is to study the competence of health counseling officer and their role in reducing mortality rates and will not focus on macroscale, which is based on data reporting.